2016
DOI: 10.21836/pem20160402
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of summer eczema using Insol® Dermatophyton – a field study

Abstract: Zusammenfassung: Empirische Studien und positive Erfahrungsberichte praktizierender Tierärzte berichten von einer Verbesserung der klinischen Sommerekzemsyptomatik nach der Behandlung mit Insol ® Dermatophyton. Ziel dieser Arbeit war es, den Einfluss von Insol ® -Dermatophyton (ID) in einer Placebo kontrollierten Blindstudie an 51 mit Sommerekzem erkrankten Pferden zu testen. Alle Pferde waren vorberichtlich am Sommerekzem erkrankt. Neben einer Allgemeinuntersuchung wurden bei der Erstuntersuchung (Februar des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Anecdotal reports indicated that treatment of horses with a vaccine against dermatophytosis reduced clinical signs of IBH, possibly by redirecting the immune response from Th2 towards Th1. A placebo-controlled study could, however, not demonstrate a significant improvement of clinical signs after three injections of Insol®-Dermatophyton [70]. Interestingly, an increase in serum IFN λ , TNFα and IL-10 could only be observed in the treated but not in the placebo group, indicating the induction of a Th1/Treg immune response [70].…”
Section: Other Treatment Options For Ibhmentioning
confidence: 91%
“…Anecdotal reports indicated that treatment of horses with a vaccine against dermatophytosis reduced clinical signs of IBH, possibly by redirecting the immune response from Th2 towards Th1. A placebo-controlled study could, however, not demonstrate a significant improvement of clinical signs after three injections of Insol®-Dermatophyton [70]. Interestingly, an increase in serum IFN λ , TNFα and IL-10 could only be observed in the treated but not in the placebo group, indicating the induction of a Th1/Treg immune response [70].…”
Section: Other Treatment Options For Ibhmentioning
confidence: 91%